Artificial Intelligence in Mathematics Learning: Examining the Readiness of Pre-Service Mathematics Teachers - Imaludin Agus; Amanda La Hadi; Tandri Patih; Nur Isra Rasid (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2026)
The use of AI in mathematics learning plays a crucial role. However, in practice, AI has not been used optimally by teachers to support learning. This study analyses the readiness of pre-service mathematics teachers to use AI in mathematics learning. The research sample was selected purposively, consisting of 42 respondents from the Mathematics Education program at IAIN Kendari in the 2024/2025 academic year. The method used is a descriptive research design with a qualitative approach. Data were collected via Google Forms and semi-structured interviews addressing pre-service teachers' readiness across four dimensions: knowledge, technical, attitudinal, and pedagogical readiness. The data were analysed through thematic analysis involving coding, categorising, and theme development, supported by technical triangulation between questionnaire responses and interview data. The results show that all pre-service mathematics teachers demonstrate knowledge readiness regarding the types of AI frequently used, including ChatGPT, Blackbox AI, Gemini, Photomath, Deepseek, and Mathway. Regarding technical readiness, 40 respondents (95.2%) reported that they can use AI, whereas 2 (4.8%) reported that they cannot. They use AI to compile learning materials, solve problems, and develop instruments. The attitudinal readiness was assessed as follows: 2 respondents (4.8%) were very confident, 29 (69%) were confident, and 11 (26.2%) were not confident. Regarding pedagogical readiness, 3 respondents (7.1%) reported being very ready to integrate AI into mathematics learning, 34 (81%) were ready, and 5 (11.9%) were not ready. The results indicate that pre-service mathematics teachers are generally ready to utilise AI in mathematics learning, but need to be supported by training, policy, and other supporting facilities.